2017
DOI: 10.5762/kais.2017.18.1.141
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Fecal Bacterial Diversity in Dogs

Abstract: In this study, a meta-analysis of fecal bacteria in dogs was conducted using 16S rRNA gene sequences that have been recovered from cloning and Sanger sequencing. For this meta-analysis, we retrieved all 16S rRNA gene sequences recovered from fecal bacteria in dogs in the RDP database (Release 11, Update 3). A total of 420 sequences were identified from the RDP database, 42 of which were also recovered from cultured isolates. The 420 sequences were assigned to five phyla, of which Firmicutes was the most predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Therefore, having a different-gender friend may be easily noticeable by others and tends to be regarded as having a romantic relationship. While the gender heterogeneity of peer groups does not necessarily indicate a romantic relationship, several studies have reported that such relationships occur more frequently in mixed-gender schools [ 46 ] and are associated with adverse outcomes such as lower ego identity and ego resilience [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, having a different-gender friend may be easily noticeable by others and tends to be regarded as having a romantic relationship. While the gender heterogeneity of peer groups does not necessarily indicate a romantic relationship, several studies have reported that such relationships occur more frequently in mixed-gender schools [ 46 ] and are associated with adverse outcomes such as lower ego identity and ego resilience [ 47 ].…”
Section: Introductionmentioning
confidence: 99%